Questioning the Buddha: a selection of twenty-five sutras - Skilling, Peter (Classics of Indian Buddhism, 2021)
"In the forty-five years the Buddha spent traversing northern India centuries before the common era, he shared his wisdom with everyone from beggar women to kings. Hundreds of his discourses, or sūtras, were preserved by his followers, first orally and later in written form. Around 800 CE they were translated into the Tibetan language, where they have been preserved ever since. To date, only a fraction of these sūtras have been made available in English. Questioning the Buddha brings the reader directly into this literary treasure with thoroughly annotated translations of twenty-five different sūtras. Often these texts, many translated here in full for the first time, begin with an encounter in which someone poses a question to the Buddha. Peter Skilling, an authority on early Buddhist epigraphy, archaeology, and textual traditions, has been immersed in the Buddhist scriptures of diverse traditions for nearly half a century. In this volume, his deep comprehension is harnessed to render these ancient teachings in a fresh and precise language. His introduction is a fascinating survey of sūtra study in the West, from its origins to today. Sūtras translated : I. Dogma, Dharma, and Ritual 1. Four Dharmas Not to Be Taken for Granted 2. The Benefits of Giving 3. The Exposition of Four Dharmas 4. Measuring the Merit of the Three Refuges 5. Four Dharmas Never to Be Abandoned 6. Teaching Given to Bodhisatva Dharmaketu 7. Teaching Given to Bodhisatva Jayamati 8. Sūtra Comparing Bodhicitta to Gold 9. Bodhisatva Maitreya's Question about the Gift of the Dharma 10. Four Summaries of the Dharma Spoken to the Nāga King Sāgara 11. The Merit of the Stanza of Dependent Arising 12. The Heart-Formula of Dependent Arising II. Marvelous Children, Women, and Gods 13. The Prediction of the Future Buddhahood of the Boy Brahmaśrī 14. Kṣemavatī's Prediction to Buddhahood 15. The City Beggar Woman 16. An Old Woman's Questions about Birth and Death 17. The Questions of Śrīmatīthe Brahman Woman 18. The Questions of the Laywoman Gaṅgottarā 19. Brahmā Sahāṃpati's Question III. Conversations with Kings 20. The Buddha's Advice to King Prasenajit 21. The Process of Rebirth 22. Instructions for King Bimbisāra 23. Instructions for King Udayana IV. The Range of the Buddhas 24. Buddhas as Rare as a Grain of Golden Sand 25. Teachings Delivered on the Occasion of the Great Final Nirvāṇa"--